Prosedur Penagihan Pajak Melalui Surat Teguran dan Surat Paksa Dalam Perspektif Ekonomi Syariah di Kantor Pelayanan Pajak Pratama Ngawi - Kasmiati Kasmiati; Jullio Fandy Krisma (LABATILA: Jurnal Ilmu Ekonomi Islam, 2022)
Taxation is a potential source of revenue to support national development. One of the efforts taken by the Director General of Taxes is to increase tax revenue through billing. Tax collection via letters of warning and coercion to raise public awareness of responsibility and role in the country's development. However, these efforts have not yet reduced tax arrears. This is proof that billing is not optimal. The purpose of this research is to analyze tax collection procedures using letters of reprimand and forced letters as well as tax collection constraints from an Islamic economic perspective. This research is a type of qualitative descriptive research that uses primary data as the main source of information and secondary data as support. Primary data was collected through interviews and observation, while secondary data was collected through documentation. The results of this study indicate that the billing implementation procedure is in accordance with the rules and principles of Islamic economics. However, in submitting letters, there are several obstacles, including the low knowledge of taxpayers, discrepancies and limited data related to taxpayers, and the inability of taxpayers who then apply for payment installments.